2008
DOI: 10.1007/s10709-008-9279-1
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to genetic quality in the context of sexual selection

Abstract: This special issue of Genetica brings together empirical researchers and theoreticians to present the latest on the evolutionary ecology of genetic quality in the context of sexual selection. The work comes from different fields of study including behavioral ecology, quantitative genetics and molecular genetics on a diversity of organisms using different approaches from comparative studies, mathematical modeling, field studies and laboratory experiments. The papers presented in this special issue primarily foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The evolutionary significance of mate choice for indirect genetic benefits is a much debated topic (e.g. Pitcher & Mays 2008; Puurtinen et al. 2009; Roberts 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolutionary significance of mate choice for indirect genetic benefits is a much debated topic (e.g. Pitcher & Mays 2008; Puurtinen et al. 2009; Roberts 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The evolutionary significance of mate choice for indirect genetic benefits is a much debated topic (e.g. Pitcher & Mays 2008;Puurtinen et al 2009;Roberts 2009). It has been suggested that if mating is usually non-random and if it usually takes indirect genetic benefits into account, enforced random mating (as, for example, in hatcheries) would negatively affect the average genetic quality of future generations Wedekind 2002a).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent surge in interest among evolutionary biologists in elucidating the genetic determinants of phenotypic quality [1,2]. This has been driven in part by researchers working in the field of sexual selection, who have sought to address whether females might acquire indirect genetic benefits for their offspring by mating with males of particular genotypes.…”
Section: Introductionmentioning
confidence: 99%